Pergeseran Legitimasi Sosio-Kultural dalam Politik Identitas Lokal: Studi Politik Genealogis Dan Elektoral Di Pilkades Tohe Leten Kecamatan Raihat Kabupaten Belu Provinsi Nusa Tenggara Timur Tahun 2019 - Engelbert Talok, Yonas; Basa Alim Tualeka; Frederick Fernandez (Journal Governance and Politics (JGP), 2025)
This thesis explores the dynamics of identity politics and the shifting socio-cultural legitimacy in the 2019 village head election (Pilkades) of Tohe Leten, located in Raihat Subdistrict, Belu Regency, East Nusa Tenggara, Indonesia. The study focuses on how traditional genealogical-based leadership selection patterns have gradually shifted towards more functional and inclusive political preferences, driven by social proximity, economic programs, and performance-based legitimacy. Using a qualitative descriptive method, data were collected through in-depth interviews, participatory observation, and document analysis. The theoretical framework draws on identity politics and Gramscian cultural hegemony to analyze the articulation of power, identity, and legitimacy in the rural electoral context.The findings reveal that while genealogical identity (uma or clan affiliation) still holds symbolic weight in village campaigns, it is no longer the sole determinant of electoral success. The victory of Wilhelmus Bau, a candidate from the minority Bunak ethnic group with non-dominant genealogical ties, signifies a major shift toward representational-functional legitimacy.This shift is further influenced by everyday socioeconomic challenges, mobile communication technology, and the evolving expectations of village constituents. Identity politics in Tohe Leten has thus transitioned from being rigidly primordial to becoming more strategic, adaptive, and performance-oriented, reflecting a deepening of democratic engagement at the village level.